Carbon nano bowl array derived from a corncob sponge/carbon nanotubes/polymer composite and its electrochemical properties. (20th October 2019) - Fang, Zeming; Cao, Lin; Lai, Fenglin; Kong, Debin; Du, Xusheng; Lin, Huaijun; Lin, Zhidan; Zhang, Peng; Li, Wei
Abstract: In this paper, carbon nano bowl array with an octopus sucker-like morphology was fabricated for the first time. A ternary corncob sponge/carbon nanotube/ethylene-vinyl acetate copolymer (CS/CNT/EVA) composite was used as the carbon source and turned into a nano bowl array after a one-step heat treatment. The corncob sponge substrate was carbonized to be a honeycomb-like sponge composed of carbon sheets, and carbon nano bowls originate from EVA were generated on the sheets due to the comprehensive effects of surfactants and CNT, resulting in a carbon nano bowl array structure. This structure endowed the resulting material with a high capacitance of 213.4 F g −1 at a current density of 0.5 A g −1, good rate ability and excellent cycling stability with a loss of less than 2% over 10000 cycles. The solid-state capacitors assembled possess a good energy density of 0.98 W h kg −1 at a power density of 8000 W kg −1 . These findings show that our method for fabricating a new kind of carbon nanostructures is promising and that the material obtained is a candidate for supercapacitor electrodes.